Construction of a risk assessment model for falls in the elderly (老年人跌倒风险评估模型的构建) - ZHAO Dan (赵丹); QI XiaoJiu (齐晓玖); CHEN Shanshan (陈闪闪); GUO Hong (郭红) (Journal of International Translational Medicine Limited, 2022)
Objective To explore the establishment of a comprehensive risk assessment model for falls in the elderly people in China. Methods Meta-analysis reappraisal combined with structured expert consultation were used to screen out risk factors for falls and OR values into the model, and established a logistic regression comprehensive evaluation model. Results The model finally included 32 indicators: age, history of falls, exercise, use of walking aids, Abnormal gait, abnormal balance, sleep disturbance, cognitive impairment, frailty, urinary/fecal incontinence, dizziness/vertigo, visual impairment, hearing impairment, lower extremity arthritis, History of stroke, diabetes, orthostatic hypotension, Parkinson's, dementia, anemia, arrhythmia, depression, foot diseases, antipsychotics, antidepressants, hypnotic sedatives, antiepileptics, opioids , loop diuretics, cardiac glycosides, hypoglycemic agents, laxatives. Conclusion Based on meta-analysis and experts' opinions, this study established a risk assessment model for falls in elderly people in China, which effectively avoided the problem of small sample size. The model was based on evidence-based medicine, and provided a basis and guidance for the screening and intervention of high-risk groups. (目的 探讨构建适用于中国老年人跌倒风险综合评估模型。方法 利用Meta分析再评价结合结构式专家咨询筛选出跌倒危险因素和OR值纳入模型, 建立logistic回归综合评估模型。结果 模型最终纳入32个指标: 年龄、跌倒史、运动、使用助行器、步态异常、平衡异常、睡眠障碍、认知障碍、衰弱、尿/便失禁、头晕眩晕、视力障碍、听力障碍、下肢关节炎、脑卒中史、糖尿病、体位性低血压、帕金森、痴呆、贫血、心律失常、抑郁、足部问题、抗精神病药、抗抑郁药、催眠镇静类药物、抗癫痫药、阿片类药物、髓袢利尿剂、强心苷类、降糖药、泻药。结论 本研究以Meta分析为基础, 结合专家意见建立了中国老年人跌倒风险评估模型, 有效避免了样本量偏少的问题, 模型基于循证医学依据, 为跌倒高危人群筛查与干预实施提供了依据和指导。)